Novel Transgastric Endoluminal Segmental Esophagectomy and Primary Anastomosis Technique: A Hybrid Transgastric Thoracoscopic Esophagectomy for the Treatment of High Grade Dysplasia and Early Esophageal Cancer in a Porcine Ex vivo Model - Kvasha, Anton; Khalifa, Muhammad; Biswas, Seema; Farraj, Moaad; Bramnik, Zakhar; Waksman, Igor (Frontiers in Surgery, 2021)
Multiple modalities are currently employed in the treatment of high grade dysplasia and early esophageal carcinoma. While they are the subject of ongoing investigation, surgery remains the definitive modality for oncological resection. Esophagectomy, however, is traditionally a challenging surgical procedure and carries a significant incidence of morbidity and mortality. Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are considerably less invasive alternatives to esophagectomy in the diagnosis and treatment of high grade dysplasia, early esophageal squamous cell carcinoma and adenocarcinoma. However, many early esophageal cancer patients, with favorable histology, who could benefit from endoscopic resection, are referred for formal esophagectomy due to lesion characteristics such as unfavorable lesion morphology or recurrence after previous endoscopic resection. In this study we present a novel, hybrid thoracoscopic transgastric endolumenal segmental esophagectomy with primary anastomosis for the potential treatment of high grade dysplasia and early esophageal cancer in a porcine ex vivo model as a proposed bridge between endoscopic resection and the relatively high mortality and morbidity formal esophagectomy procedure. The novel technique consists of thoracoscopic esophageal mobilization in addition to transgastric endoluminal segmental esophagectomy and anastomosis utilizing a standard circular stapler. The technique was found feasible in all experimental subjects. The minimally invasive nature of this novel procedure as well as the utility of basic surgical equipment and surgical skill is an important attribute of this method and can potentially make it a treatment option for many patients who would otherwise be referred for a formal esophagectomy.